Food Security and the Modernisation Pathway in China Towards Sustainable Agriculture - Schwoob, Marie-Hélène (Critical Studies of the Asia-Pacific, 2018)
This book aims at providing students, experts and practitioners with a detailed overview of agricultural and food security issues in China, analyzed through the lenses of a multidisciplinary approach that enables to fully grasp the current socio-political challenges and lock-ins of agricultural transformation towards more sustainable practices. Confronted to a running decrease and degradation of its resources and rapidly evolving food habits, China became a net importer of food in 2004, and its agricultural balance has since become heavier every day. Beyond providing a comprehensive overview of these stakes, this book also presents consistent and original first hand research material, collected by the author during months of fieldwork in China, in the countryside and from various economic and political circles. Conclusions drawn from this often difficult to access) fieldwork shed light on the whole galaxy of public and private stakeholders taking part in agricultural modernization in China, on their interests and on the patterns of power that underlie the development and implementation of agricultural policies. .